2022
DOI: 10.3390/ijerph19063542
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Spraying of Selenium Combined with Biochar Alleviates Cadmium Toxicity in Peanuts and Enriches Selenium in Peanut Grains

Abstract: Cadmium (Cd) pollution in soil, particularly in peanut production, is a problem that has attracted global concern and needs solutions urgently. Selenium (Se) can alleviate Cd toxicity; however, the underlying mechanisms are not completely understood. Therefore, two varieties of peanut (Arachis hypogaea Linn.), “Huayu 23” and “Huayu 20”, were chosen as the target crops for this study. A pot experiment was conducted to investigate the effects of two Se application methods combined with biochar on the accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…By adding different concentrations of CdCl 2 and sodium selenite in the wheat hydroponic experiment, Se was found to limit the accumulation of Cd in wheat plants by regulating the subcellular distribution and chemical morphology of Cd in wheat tissues and the expression of TaNramp5-a, TaNramp5-b and TaHMA 2 in the roots [ 49 ]. Meanwhile, antagonism between Se and Cd has been found in other crops [ 50 , 51 , 52 ]. Therefore, the application of SOF in this study may have driven the wheat plants to directly inhibit the uptake of Cd at the wheat rhizosphere, thus effectively reducing the Cd content of the wheat grains.…”
Section: Discussionmentioning
confidence: 99%
“…By adding different concentrations of CdCl 2 and sodium selenite in the wheat hydroponic experiment, Se was found to limit the accumulation of Cd in wheat plants by regulating the subcellular distribution and chemical morphology of Cd in wheat tissues and the expression of TaNramp5-a, TaNramp5-b and TaHMA 2 in the roots [ 49 ]. Meanwhile, antagonism between Se and Cd has been found in other crops [ 50 , 51 , 52 ]. Therefore, the application of SOF in this study may have driven the wheat plants to directly inhibit the uptake of Cd at the wheat rhizosphere, thus effectively reducing the Cd content of the wheat grains.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested the importance of soil factors and the potential of appropriate agronomic practices in controlling Cd contamination in peanut. In a pot experiment, Shao et al (2022) demonstrated that foliar spray of selenium combined soil application of biochar signi cantly reduced Cd accumulation in peanut kernels. The effectiveness of similar agronomic measures under eld production conditions merits further attention.…”
Section: Discussion Andmentioning
confidence: 99%
“…In China, hazardous metals have polluted around 2.0 × 10 7 hm 2 of arable land, and 2.8 × 10 5 hm 2 of farmland is contaminated with cadmium [4]. Due to its high toxicity, lengthy half-life, and difficulty in transformation and breakdown [5], the heavy metal element Cd poses a significant risk to soil-dwelling plant life, particularly crop growth. According to Zhang et al [6], the primary way that Cd enters the human body is through the consumption of agricultural byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium has been shown to have a mitigating effect on Cd stress in a number of crops, including radish [33], rice [34][35][36], peanuts [5], wheat [37], maize [38], and oilseed rape [39,40]. However, relatively few studies have been done on purple flowering stalks as a plant, and it is still unclear how selenium influences the plant's defense mechanism against Cd stress at the molecular, biochemical, and physiological levels [41].…”
Section: Introductionmentioning
confidence: 99%